2011
DOI: 10.4028/www.scientific.net/amm.145.455
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Drought Prediction Using Support Vector Machines

Abstract: In Taiwan, even though the average annual rainfall is up to 2500 mm, water shortage during the dry season happens sometimes. Especially in recent years, water shortage has seriously affected the agriculture, industry, commerce, and even the essential daily water use. Under the threat of climate change in the future, efficient use of water resources becomes even more challenging. For a comparative study, support vector machine (SVM) and other three models (artificial neural networks, maximum likelihood classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…SVR has a simple geometric representation, and it does not depend on the dimensionality of the input data. Although SVR has been applied in several hydrology problems, such as predicting stream flow (flood) (Behzad et al, 2009;Chen and Yu, 2007), soil moisture (Ahmad et al, 2010;Pasolli et al, 2011) and droughts (Chiang and Tsai, 2012;Ganguli and Reddy, 2013), this method has not yet been fully explored in predicting stream temperature.…”
Section: ! !mentioning
confidence: 99%
“…SVR has a simple geometric representation, and it does not depend on the dimensionality of the input data. Although SVR has been applied in several hydrology problems, such as predicting stream flow (flood) (Behzad et al, 2009;Chen and Yu, 2007), soil moisture (Ahmad et al, 2010;Pasolli et al, 2011) and droughts (Chiang and Tsai, 2012;Ganguli and Reddy, 2013), this method has not yet been fully explored in predicting stream temperature.…”
Section: ! !mentioning
confidence: 99%
“…The results suggested that XGBoost had high predictive skill compared to the lag distributed non-linear model (DLNM). In another study, Chiang and Tsai [31] found SVM (Support Vector Machine) superior in predicting hydrological drought compared to the traditional model. In some cases, however, the performance of deep learning in drought studies exceeds other machine learning models [28].…”
Section: Introductionmentioning
confidence: 99%
“…Another machine learning algorithm that appears to be successful in hydrological predictions is support vector machine (SVM), which is also called support vector regression (SVR) when applied to function approximation or time series predictions. SVMs have been successfully applied to time series forecasting [9], the stock market [10] and in particular, water-related applications for the prediction of wave height [11]), the generation of operating rules for reservoirs [12], drought monitoring [13], water level prediction [14], and short-and long-term flow forecasting [15], among others. Overfitting and local optimal solution are unlikely to occur with an SVM, and this enhances the performance of SVM for the prediction.…”
Section: Introductionmentioning
confidence: 99%